Perceived health in the Portuguese population aged ? 35 - Figueiredo, João Paulo de; Cardoso, Salvador Massano (Revista de Saúde Pública, 2014)
OBJECTIVE : To evaluate the exploratory relationship between determinants of health, life satisfaction, locus of control, attitudes and behaviors and health related quality of life in an adult population. METHODS : Observational study (analytical and cross-sectional) with a quantitative methodological basis. The sample was composed oy 1,214 inhabitants aged ≥ 35 in 31 civil parishes in the County of Coimbra, Portugal, 2011-2012. An anonymous and voluntary health survey was conducted, which collected the following information: demographic, clinical record, health and lifestyle behaviors; health related quality of life (Medical Outcomes Study, Short Form-36); health locus of control; survey of health attitudes and behavior, and quality of life index. Pearson’s Linear Correlation, t-Student, Wilcoxon-Mann-Whitney; One-way ANOVA; Brown-Forsythe’s F; Kruskal-Wallis; Multiple Comparisons: Tukey (HSD), Games-Howell and Conover were used in the statistical analysis. RESULTS : Health related quality of life was shown to be lower in females, in older age groups, in obese/overweight individuals, widows, unassisted, those living alone, living in rural/suburban areas, those who did not work and with a medium-low socioeconomic level. Respondents with poor/very poor self-perceived health (p < 0.0001), with chronic disease (p < 0.0001), who consumed < 3 meals per day (p ≤ 0.01), who were sedentary, who slept ≤ 6 h/day and had smoked for several years revealed the worst health results. Health related quality of life was positively related with a bigger internal locus, with better health attitudes and behaviors (physical exercise, health and nutritional care, length of dependence) and with different areas of life satisfaction. CONCLUSIONS : Better health related quality of life was associated with certain social, psychological, family and health characteristics, a satisfactory lifestyle, better socioeconomic conditions and a good internal locus of control over health attitudes and behaviors.